Polymorphisms of the sodium voltage-gated channel, alpha subunit 1 (SCN1A -A3184G) gene among children with non-lesional epilepsy: a case-control study - Esraa Ghazala; Doaa A. Shahin; Yahya Wahba (BMC, 2022)
Abstract Background Mutations in the neuronal sodium voltage-gated channel, alpha subunit 1 (SCN1A) gene have been associated with epilepsy. We investigated the SCN1A-A3184G polymorphism among Egyptian children and adolescents with non-lesional epilepsy. Methods A prospective case - control observational study was done in Mansoura University Children's Hospital, Egypt including 326 children with non-lesional epilepsy (163 antiepileptic drugs (AEDs) resistant cases & 163 AEDs responders) and 163 healthy controls. One step real time polymerase chain reaction (PCR) was used for the molecular analysis. Student's t-test, and Monto Carlo, chi-square and Mann-Whitney tests were used for the statistical analysis. Results All study participants were matched as regards the age, sex and body weight (p = 0.07, 0.347 and 0.462, respectively). They had the (AA) and (AG) genotypes but not the (GG) variant. No significant differences were found between cases and controls regarding (AG) and (AA) genotypes and A- and G-alleles (p = 0.09 and 0.3, respectively). We did not find significant differences between AEDs responders and resistant cases regarding the studied genotypes and alleles (p = 0.61 and 0.746, respectively). In the resistant group, we observed significant associations between the (AG) genotype and seizure frequency (p = 0.05), the tonic-clonic seizure (p < 0.001), the younger age of first seizure attack (p = 0.03), abnormal electroencephalogram (EEG) (p < 0.001), the positive family history of epilepsy (p = 0.006), topiramate (p = 0.03) and valproic acid (p < 0.001), while the (AA) genotype was associated with carbamazepine (p = 0.03). While in AEDs responders, there were significant associations between the AG genotype and the abnormal EEG activity, levetiracetam and carbamazepine (p = 0.016, 0.028 and 0.02). Conclusions The SCN1A-A3184G genotypes and alleles were not associated with the epilepsy risk among Egyptian children. Significant associations were reported between the AG genotype and some predictors of refractory epilepsy.